Comparison of the sealing ability of various bioceramic materials for endodontic surgery - Benjamin Rencher; Ana M. Chang; Hanson Fong; James D. Johnson; Avina Paranjpe (Restorative Dentistry & Endodontics, 2021)
ObjectivesEndosequence Bioceramic Root Repair Material (BC-RRM) is used in endodontic microsurgery. It is available as a paste and a putty. However, no studies to date have examined the sealing ability of these forms alone or in combination as root-end filling materials. Hence, this study aimed to compare the sealing properties of these 2 forms of BC-RRM.Materials and MethodsForty-two extracted upper anterior teeth were divided into 3 experimental groups, a positive and negative control. After the root canal treatment, the root ends were resected, retroprepared and retrofilled with either putty, paste + putty or mineral trioxide aggregate (MTA). The teeth were mounted in tubes so the apical 3 mm was submerged in Brain Heart Infusion (BHI) broth. The coronal portions of the canals were inoculated with Enterococcus faecalis and BHI broth and incubated for 30 days. The broth in the tubes was analyzed for colony forming units to check for leakage of bacteria from the canal. The teeth from the groups were sectioned and analyzed using scanning electron microscopy (SEM). The Kruskal-Wallis test and analysis of variance were used to analyze the data with a significance level p < 0.05.ResultsThe BC-RRM and MTA groups showed similar sealing ability. The positive control showed leakage in all samples. The SEM imaging showed the presence of bacteria in all experimental groups at the material-tooth interface.ConclusionsNo significant differences were noted in the experimental groups, providing sufficient evidence that any combination could be effectively used during endodontic microsurgery.